Nurturing transgenerational entrepreneurship in ethnic Chinese family SMEs: exploring Indonesia. Issue 2 (21st March 2019) - Tan, Jacob Donald; Supratikno, Hendrawan; Pramono, Rudy; Purba, John Tampil; Bernarto, Innocentius
Abstract : Purpose: This paper aims to explore and explain how predecessors (incumbents) of ethnic Chinese family small and medium-sized enterprises (SMEs) in Indonesia or appropriately called Chinese-Indonesian family SMEs nurture their successors in procuring transgenerational entrepreneurship. Design/methodology/approach: A total of 25 participants were involved in this qualitative study which employed a multi-method triangulation design with the following research instruments: semi-structured in-depth interviews with experts, incumbents and successors of Chinese-Indonesian family SMEs, field notes from conversations and observations during engagement with participants affiliated to the family SMEs, a focus group discussion with academicians and literature reviews. Another key approach is source triangulation, where different participants – e.g. from among the experts, from among the incumbents, successors and family members in each family business case were interviewed and engaged outside the interview sessions. Findings: The proposed theoretical framework depicts comprehensive attributes of nurturing Chinese-Indonesian successors to continue enterprising at the helm of family SMEs. Propositions are used to explain the impacts these attributes have on transgenerational entrepreneurship specifically. At the personal level, incumbents have to focus on discovering the successors' passions and nurture them in formal education, childhood involvement, as well as bridging them in entrepreneurial knowledge through cultural values, mentorship, autonomy and role modelling. Incumbents also had to plan for their retirements to provide autonomy for successors. At the firm/family level, incumbents must be able to set a foothold on family governance, firm governance and ownership distribution to reduce conflicts in their family businesses. Furthermore, as a minority group with past traumatic experiences, Chinese-Indonesian family SMEs usually equip themselves with contingency plans to protect their assets for the long-term future. Research limitations/implications: This study was conducted in Indonesia amongst Chinese-Indonesian family SMEs and thus it is not generalisable in other settings. Literature reviews on family SMEs succession are still scant, especially on the Chinese-Indonesian. Practical implications: Predecessors/incumbents of Chinese-Indonesian family SMEs could consider implementing the proposed nurturing strategies to their successors to sustain the longevity of the business based on trust, stewardship and harmony. The theoretical research framework resulted from this study offers general suggestions on how to nurture the next generation specifically from personal/interpersonal perspectives, which must be accompanied by specific scopes of family and firm aspects. This study extends beyond indicating the factors (ingredients) by explaining how to nurture transgenerational entrepreneurship (cook the ingredients) in SMEs for a tactful transition. Hence, the incumbents play vital roles and must be poised to adjust their mindsets to certain aspects indicated in this study. Social implications: Most overseas Chinese businesses are family-owned, and besides Indonesia constituting the largest Chinese population outside the Republic of China, this 3 per cent of Indonesia's people are known for controlling about 70 per cent of the economy. Furthermore, SMEs play a significant role in the Indonesian economy, as they provide about 97 per cent off the country's employment and 57.8 per cent of the gross domestic product. Hence, the longevity of Chinese-Indonesian family SMEs must be well managed to bolster the economy and social welfare of the country. Originality/value: A transgenerational entrepreneurship model in the context of Chinese-Indonesian family SMEs which incorporates the nurturing process of the successor to step up the helm of the business is proposed in the study.